2017
DOI: 10.3390/bs7010011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Philosophies Underpinning Dietetic Private Practice

Abstract: There is limited theory or knowledge regarding dietitians’ practice philosophies and how these philosophies are generated and incorporated into their professional practices. For the purposes of this study, a conceptual framework will explain and define the ‘philosophies’ as three different types of knowledge; episteme, techne, and phronesis. This study aimed to develop an explanatory theory of how dietitians in private practice source, utilise, and integrate practice philosophies. A grounded theory qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Given that primary care dietitians are paid per consultation rather than according to time worked, time was seen by some participants as a constraint that could negatively impact client care. The risks to effectiveness of time constraints supports the findings of other studies suggesting that sacrificing consultation time for financial remuneration impedes the perception of quality and effectiveness of the nutrition care provided . Reducing consultation time in line with the level of state funded remuneration in Australia may therefore prevent optimal client care .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Given that primary care dietitians are paid per consultation rather than according to time worked, time was seen by some participants as a constraint that could negatively impact client care. The risks to effectiveness of time constraints supports the findings of other studies suggesting that sacrificing consultation time for financial remuneration impedes the perception of quality and effectiveness of the nutrition care provided . Reducing consultation time in line with the level of state funded remuneration in Australia may therefore prevent optimal client care .…”
Section: Discussionsupporting
confidence: 78%
“…Dietitians in the present study perceived that the ability to balance efficiency and effectiveness was something that grew with experience or through increased support from other primary care dietitians. Previous research has found that, although some dietitians are content to work in isolation, most feel that support from other dietitians is important for the growth of individuals and the profession . Working in a multidisciplinary team has previously been found to improve practice through: (i) more appropriate referrals; (ii) increased support for areas outside of dietitians’ scope of practice; and (iii) opportunities to facilitate consistent nutrition messages by practice teams .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary care dietitians have identified sophisticated processes to identify, generate, retain and expand the services they provide. Although business acumen (30) and aspects of identification and retention of clients to a clinical service has been discussed by others (29,31) , this study has identified the intricate relationship these aspects have to fundamental financial measures to ensure practice viability. Although, most participants had no formalised business training, many had upskilled by seeking specific training or mentoring.…”
Section: Discussionmentioning
confidence: 98%
“…The context in which clinical decisions are made can impact on the process of CDM and also on what decisions can be made by the dietitian for patient care ( 11–14 ) . Little research has been undertaken that explores the influence of practice setting and its various characterising elements on dietitians’ CDM.…”
Section: Introductionmentioning
confidence: 99%